Menggali Eksistensi Rainsford dan Zaroff, Analisis Filosofis terhadap The Most Dangerous Game Karya Richard Connell - Edria Sandika (Politeknik Negeri Padang, 2014)
This article discusses famous short story by Richard Connell entitled The Most Dangerous Game. It seek to explore themeaning of main characters’ existence from philosophical perspective. The finding of this article is that both main characters (Zaoffand Rainsford) each represent the concept of bad faith and authentic in search of their existence. This short stories itself alsorepresents the importance of existence/survival facing the reality of hunting and being hunted.